Entrepreneurial Values in The Management of The Family Kitchen (Purga) At Al-Amien Prenduan Islamic Boarding School - Wardi, Moh.; Agustina, Sri; Hodairiyah, Hodairiyah (LPPPM STAI Darul Hikmah Bangkalan, 2025)
The purpose of this study is to find out the values of religious, educational, and economy of Abdhi Dhalem or servant in family kitchen or Dapur Keluarga (Purga). This study employs a qualitative descriptive methodology, and the organizers of the family kitchen and a number of servants serve as the sources of research data. According to the study's findings, the Abdhi Dhalem of the family kitchen demonstrates the importance of honesty in adhering to the Pondok's (boarding school) standard of menus. Amanah or responsibility values the equitable fulfilment of students' rights and responsibilities. Second, entrepreneurial principles through instruction and financial literacy role models for family teachers, handling cash inflows and outflows for the needs of kitchen supplies or student meal costs properly and correctly.